Electronic Health Records Are the Next Frontier for the Genetics of Substance Use Disorders. Issue 5 (May 2019) - Sanchez-Roige, Sandra; Palmer, Abraham A.
Abstract : Compared with other psychiatric disorders of similar heritabilities, the progress of substance use disorders (SUD) genetics has been slow. With the growing availability of large-scale biobanks with extensive phenotypes from electronic health records (EHR) and genotypes across millions of individuals, this platform is the next tool to accelerate SUD genetics research.